The influence of crystallization route on the properties of lanthanum-doped Bi4Ti3O12 thin films prepared from polymeric precursors - Simoes, A. Z.; Riccardi, C. S.; Quinelato, C.; Ries, A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
Pure and lanthanum-doped Bi4Ti3O12 thin films were deposited on Pt/Ti/SiO2/Si substrate using a polymeric precursor solution. The spin-coated films were specular and crack-free and crystalline after annealing at 700 degreesC for 2 h. Crystallinity and morphological evaluation were examined by X-ray diffraction (XRD), scanning electron microscopy (SEM), and atomic force microscopy (AFM). Multilayered films obtained using the intermediate-crystalline layer route present a dense microstructure with spherical grains. Films obtained using the intermediate-amorphous layer, present elongated grains around 250 nm in size. The dielectric and ferroelectric properties of the lanthanum-doped Bi4Ti3O12 films are strongly affected by the crystallization route. The hysteresis loops are fully saturated with a remnant polarization and drive voltage of the films, heat-treated by the intermediate-crystalline (P-r = 20.2 muC/cm(2) and V = 1.35 V) and for the film heat-treated by amorphous route (P-r = 22.4 muC/cm(2) and V = 2.99 V). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: ceramics; electrical measurements; film deposition; thin films